2022
DOI: 10.3389/fcell.2022.814746
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Arm Regeneration: Label-Free Multiphoton Microscopy to Dissect the Process in Octopus vulgaris

Abstract: Cephalopod mollusks are endowed with an impressive range of features that have captured the attention of scientists from different fields, the imaginations of artists, and the interests of the public. The ability to spontaneously regrow lost or damaged structures quickly and functionally is among one of the most notable peculiarities that cephalopods possess. Microscopical imaging techniques represent useful tools for investigating the regenerative processes in several species, from invertebrates to mammals. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Recently, cephalopod arm wound healing was subjected to closer investigation (Shaw et al, 2016): wound closure was followed for the first 24 h after amputation in O. vulgaris, using classical histological staining, immunohistochemistry (IHC), high-resolution ultrasound imaging and electron microscopy. Despite the diverse experimental settings (water temperature, animals' age, species, sex, surgical method, site of lesion) the newer studies (Tressler et al, 2014;Shaw et al, 2016;Imperadore et al, 2022) confirm the earlier macro-and microscopic accounts, and especially the key role of amoebocytes/hemocytes (Polglase et al, 1983;Imperadore, et al, 2022). Shaw et al (2016) also suggested i. a role for muscles cells in plug development, ii.…”
Section: Arm and Pallial Nerve I From Lesion To Recoverymentioning
confidence: 97%
See 2 more Smart Citations
“…Recently, cephalopod arm wound healing was subjected to closer investigation (Shaw et al, 2016): wound closure was followed for the first 24 h after amputation in O. vulgaris, using classical histological staining, immunohistochemistry (IHC), high-resolution ultrasound imaging and electron microscopy. Despite the diverse experimental settings (water temperature, animals' age, species, sex, surgical method, site of lesion) the newer studies (Tressler et al, 2014;Shaw et al, 2016;Imperadore et al, 2022) confirm the earlier macro-and microscopic accounts, and especially the key role of amoebocytes/hemocytes (Polglase et al, 1983;Imperadore, et al, 2022). Shaw et al (2016) also suggested i. a role for muscles cells in plug development, ii.…”
Section: Arm and Pallial Nerve I From Lesion To Recoverymentioning
confidence: 97%
“…The different settings, however, may influence events, pathways, and mechanisms underlying healing and regeneration. How the problem of ecological validity can be profitably overcome, is suggested by a recent work on O. vulgaris ( Imperadore et al, 2022 ). The study took advantage of the high incidence of damaged wild-caught animals for this species, reported to occur at a rate of around 51% in the Gulf of Naples ( Florini et al, 2011 ) and apparently linked to sublethal predation, autophagy, mating and aggressive behaviours (see Imperadore and Fiorito, 2018 ) for testing label-free multiphoton microscopy in the investigation of regeneration in cephalopods (see below).…”
Section: Cephalopod Regeneration Todaymentioning
confidence: 99%
See 1 more Smart Citation
“…In experimental neuroscience, the omission of markers allows for better comparison of preclinical data across different animal species, as the obtained information is independent of staining protocols specific to each model. For example, multimodal label-free multiphoton microscopy combining CARS, TPEF, and SHG imaging has been used in octopus PNS injury to examine the mechanisms of degeneration processes, scarring and subsequent regeneration of the pallial nerve and of the whole arm (Imperadore et al 2018 , 2022 ).…”
Section: Label-free Analysis Of Nervous Tissue In Healthy and Disease...mentioning
confidence: 99%
“…Beyond the salamander limb field, the term “blastema” has been applied more generally to describe a large variety of structures, in many species, during the regeneration of several different organ systems ( Reddien and Sánchez Alvarado, 2004 ; Bely and Nyberg, 2010 ; Fernando et al, 2011 ; Tanaka and Reddien, 2011 ; Bradshaw et al, 2015 ; Sallin et al, 2015 ; Zhao et al, 2016 ; Imperadore et al, 2017 ; 2022 ; Elchaninov et al, 2021 ; Bando et al, 2022 ; Vonk et al, 2022 ). These structures are generally superficially similar in that they consist of a mass of cells which must proliferate and repattern itself to regenerate large anatomical structures ( Bely and Nyberg, 2010 ; Tanaka and Reddien, 2011 ; Zhao et al, 2016 ; Elchaninov et al, 2021 ) .…”
Section: Introductionmentioning
confidence: 99%